KEANEKARAGAMAN BURUNG AIR DI BAGAN PERCUT, DELI SERDANG SUMATERA UTARA - Erny Jumilawaty; Ani Mardiastuti; Lilik Budi Prasetyo; Yeni Aryati Mulyani (Media Konservasi, 2011)
Mudflat in Bagan Percut plays important role for many activities of waterbirds, i.e. feeding ground, shelter and many activities social. The aim of this research was to know waterbirds diversity. This research was found 33 species (5 families) of waterbirds that use mudflat in Bagan Percut. The highest number of species (26 species) was found in October. The highest diversity (H’ = 2.59) was found in February and lowest (H’ = 1.50) in March. The value of evenness (Shannon index) was higher (0.84) in February and lowest (0.60) in March and October. Charadrius leschenaultia, C. mongolus were dominant species. This identification showed that two species Mycteria cinerea and Leptoptilos javanicus were International protected species according to Vulnerable and two species Numenius arquata and Limnodromus semipalmatus Near Threatened IUCN. Fifth teen species of them were protected in Indonesia.  Keyword: bird, bird diversity, Bagan Percut, aquatic birds, waterbirds